(untitled) - Russell, Travis (New York, 2008)
Seamlessly merge the Internet with cellular and wireless networks using next-generation IMS technology and the comprehensive information contained in this authoritative resource. The IP Multimedia Subsystem: Session Control and Other Network Operations details the steps necessary to deliver Web-based content, VoIP, streaming multimedia, conference calls, and text messages across one integrated network. Learn how to transition to IMS architecture, communicate with legacy networks, control sessions using SIP, and connect subscribers to network services. In-depth coverage of the latest IMS security, business intelligence, customer care, and billing procedures is also included
Keywords: Internet Protocol multimedia subsystem,Computer networks,Mạng máy tính; Management,Quản trị